1997
DOI: 10.1002/(sici)1099-0720(199704)11:2<163::aid-acp427>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Moveable Cues: a Practical Method for Reducing Context-Dependent Forgetting

Abstract: In three experiments subjects studied a list of words under incidental learning conditions. Their explicit memory was tested using free recall. Relearning to criterion was also measured in Experiment 3. Testing took place at intervals after the study period of either 1 hour or 48 hours, and in the same or in a different environment. In all experiments either one or two ambient environmental context cues were present at study, which were then either present or not present at test. Ambient cues were found to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Research on ''awareness'' in the performance of memory tasks has led to the distinction that has been made between implicit memory and explicit memory (Schacter, Wagner, & Buckner, 2000). Whereas there is some evidence to suggest that extra-item contexts can influence implicit memory as well as explicit memory (Parker & Gellatly, 1997), it is also clear that not all indirect tests of memory will be influenced by the reinstatement of context (Parker et al, 1999;see Murnane, Phelps, & Malmberg, 1999).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Research on ''awareness'' in the performance of memory tasks has led to the distinction that has been made between implicit memory and explicit memory (Schacter, Wagner, & Buckner, 2000). Whereas there is some evidence to suggest that extra-item contexts can influence implicit memory as well as explicit memory (Parker & Gellatly, 1997), it is also clear that not all indirect tests of memory will be influenced by the reinstatement of context (Parker et al, 1999;see Murnane, Phelps, & Malmberg, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Eich, 1985;Godden & Baddeley, 1975;Parker & Gellatly, 1997; q The authors all contributed equally to this paper. The order of authorship was determined by flipping a coin.…”
Section: Introductionmentioning
confidence: 98%
“…Despite the clear rationale underlying these predictions, as well as the fact that context-mediated facilitation of target memory is widely found when tested by free or cued recall (e.g., Parker, & Gellatly, 1997;Smith, & Manzano, 2010), CEs are difficult to produce reliably in recognition experiments (Hollingworth, 2006;Smith, & Manzano, 2010;Rutherford, 2000). Inconsistencies between studies that report CEs in recognition memory (e.g., Hollingworth, 2006;Russo, Ward, Geurts, & Scheres, 1999) and others that do not (e.g., Godden, & Baddeley, 1980;Murnane, & Phelps, 1993 contributed to Hanczakowski et al, (2014) proposition that while context reinstatement does reliably affect recognition processes, the effect is subtle and therefore not always detected by the presumably insensitive measure of recognition discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that environmental sounds that are paired with congruent images during encoding increased memory for objects within the environment (Davis et al, 1999). Using other cues (such as smell and music), Parker and Gellatly (1997) found that participants who were given the combination of cues showed better memory performance than those who were given the cues in isolation. The combination yielded the largest advantage when longer intervals were allowed between study and test (e.g., 24-48 hr).…”
Section: Augmenting Context-dependent Memorymentioning
confidence: 98%